PREFERENSI HABITAT MACAN TUTUL JAWA (Panthera pardus melas Cuvier 1809) DI JAWA BAGIAN BARAT - Hendra Gunawan; Vivin Silvaliandra Sihombing (Jurnal Penelitian Hutan dan Konservasi Alam, 2017)
ABSTRACT The Javan leopard (Panthera pardus melas Cuvier 1809) is a highly adaptable species, and therfore it can be found in most land types such as savannah, grassland, shrub, swampy tropical rain forest, steep mountain forest, dry and deciduous forest, coniferous forest, and even in the vicinity of human settlements. However, in occupying their habitat, the leopard has preferences for certain habitat features that increase their chances for survival. The objective of this research was to study the Javan leopard preferences for particular habitat features such as land type, topography, elevation, and status of forest function. Chi-square tests were applied to test the significance of the correlation between the presence of leopard and particular habitat features. Neu’s indexes were calculated to rank the preference of the leopard for the habitat features. The results showed that the Javan leopard has preferences for particular land types, elevations, topography, and forest status. These preferences were correlated with the availability of prey and shelter (cover) and disturbance by human activities. Javan leopard preferred primary forest in mountain areas with height of more than 1,000 m above sea level, steep slopes and protected area in conservation forest, which is less disturbed by human activities.Key words: Leopard, preference, habitat, selection, Panthera pardus ABSTRAKMacan Tutul Jawa (Panthera pardus melas Cuvier 1809) mudah beradaptasi dengan kondisi lingkungannya, oleh karena itu satwa ini ditemukan di setiap tipe tutupan lahan seperti savana, padang rumput, semak, hutan hujan tropis berawa, pegunungan yang terjal, hutan gugur yang kering, hutan konifer sampai sekitar pemukiman. Meskipun demikian, dalam menempati suatu habitat, Macan Tutul Jawa memiliki preferensi terhadap fitur-fitur habitat tertentu untuk menjamin kelangsungan hidupnya. Penelitian ini betujuan untuk mengetahui preferensi habitat Macan Tutul Jawa, dilihat dari tipe tutupan lahan, topografi, elevasi dan fungsi kawasan hutan. Uji Chi-square ( 2 ) dilakukan untuk mengetahui signifikansi korelasi keberadaan Macan Tutul Jawa dengan fitur habitat tertentu. Indeks Neu dihitung untuk mengetahui fitur habitat yang paling disukai oleh Macan Tutul Jawa. Hasil penelitian ini menemukan bahwa Macan Tutul Jawa memiliki preferensi terhadap tipe tutupan lahan, topografi, elevasi dan fungsi kawasan hutan. Preferensi ini diduga berkaitan dengan ketersediaan satwa mangsa, lindungan (cover) dan tingkat keamanan dari gangguan manusia. Macan Tutul Jawa menyukai tipe hutan primer di daerah pegunungan dengan ketinggian lebih dari 1.000 m dpl, berlereng curam dan terlindungi dengan status sebagai kawasan konservasi yang jauh dari gangguan aktivitas manusia.Kata kunci: Macan tutul, preferensi, habitat, seleksi, Panthera pardus